THE USE OF STIMULI IN RELIGIOUS PSYCHOLOGY: INTERACTION STRATEGIES OF INDONESIAN DIASPORA TEACHERS WITH STUDENTS AT SANGKHOM ISLAM WITTAYA SCHOOL THAILAND - Qudratullah Qudratullah (Education Studies and Teaching Journal (EDUTECH), 2025)
This study aims to analyze the use of stimuli in religious psychology as an interaction strategy between Indonesian diaspora teachers and students at Sangkhom Islam Wittaya School in Thailand. The main focus of this research is to identify and describe how teachers employ cognitive, affective, and behavioral stimuli in the process of religious education. Through interviews with diaspora teachers, it was found that the approach used involves gentleness, affection, and appreciation for students' efforts, which serve as cognitive stimuli in fostering understanding of the material. Additionally, emotional attention, empathy, and compassionate communication become effective stimuli that strengthen the emotional bond between teachers and students, encouraging student engagement and motivation. Behavioral stimuli are demonstrated through the teachers' role models, the habituation of positive attitudes, and reinforcement of good behavior through rewards and positive reinforcement. This study shows that the integration of these three types of stimuli creates a holistic learning environment that supports students' academic, emotional development.